Visuospatial Attention and Saccadic Inhibitory Control in Children With Cerebral Palsy - Maioli, Claudio; Falciati, Luca; Galli, Jessica; Micheletti, Serena; Turetti, Luisa; Balconi, Michela; Fazzi, Elisa M. (Frontiers in Human Neuroscience, 2019)
Cerebral palsy is a non-progressive syndrome due to a pre-, peri- or postnatal brain injury, which frequently involves an impairment of non-motor abilities. The aim of this paper was to examine visuospatial attention and inhibitory control of prepotent motor responses in children with cerebral palsy showing a normal IQ or mild cognitive impairment, measuring their performance in oculomotor tasks. Ten children (9-16 year-old) with spastic cerebral palsy and 13 age-matched, typically developing children participated in the study. Subjects performed a simple visually-guided saccade task and a cue-target task, in which they performed a saccade towards a peripheral target, after a non-informative visual cue was flashed 150 ms before the imperative target, either at the same (valid) or at a different (invalid) spatial position. Children with cerebral palsy showed severe executive deficits in maintaining sustained attention and complying with task instructions. Furthermore, saccadic inhibitory control appeared to be significantly impaired in presence of both stimulus-driven and goal-directed captures of attention. In fact, patients showed great difficulties in suppressing saccades not only to the cue stimuli, but also to the always-present target placeholders, which represented powerful attentional attractors that had to be covertly attended throughout the task execution. Moreover, impairment did not affect in equal manner the whole visual field, but showed a marked spatial selectivity in each individual subject. Saccade latencies in the cue-target task were faster in the valid than in the invalid condition in both child groups, indicating the preservation of low-level visuospatial attentive capabilities. Finally, this study provides evidence that these impairments of executive skills and in inhibitory control, following early brain injuries, manifest in childhood but recover to virtually normal level during adolescence.